GIMEMA survey on the management of chronic myeloid leukemia patients in the third line and beyond: insights from Italian hematologists - Breccia, Massimo; Piciocchi, Alfonso; Abruzzese, Elisabetta; Cilloni, Daniela; Castagnetti, Fausto; Messina, Monica; Soddu, Stefano; Scappini, Barbara; Markovic, Uros; Annunziata, Mario; Malato, Alessandra; Binotto, Gianni; et al. (Frontiers in Oncology, 2025)
BackgroundApproximately one-third of chronic myeloid leukemia (CML) patients may develop resistance and/or intolerance to the current therapies and need to switch to later lines of treatment. However, how to choose a later line of therapy is still a matter of discussion.MethodsA survey was performed by the Gruppo Italiano Malattie Ematologiche dell’Adulto (GIMEMA) to understand how the scenario has changed after the introduction of the first allosteric inhibitor, asciminib, in later lines.ResultsThe GIMEMA survey aimed to reassess the Italian approach to third-line or later-line treatments in CML. In the whole cohort of 1,637 patients, to treat resistance, ponatinib was used with a mean of 41% [standard deviation (SD) = 29] and a median of 50% (0–100), while asciminib was used with a mean of 27% (SD = 23) and a median of 25% (0–100). Indeed, to treat intolerance, asciminib was the most used with a mean of 32% (SD = 30) and a median of 30 (0–100), followed by bosutinib with a mean of 25% (SD = 25) and a median of 20 (0–90). Several possible treatment sequences were analyzed, and asciminib emerged as the best third-line treatment.ConclusionsThe survey attempted to understand the major reasons for treatment switch, how tyrosine kinase inhibitors (TKIs) were selected, and which drug was preferred based on patient and disease characteristics. The current algorithm of treatment seems to have changed in both resistant and intolerant CML patients in later lines. The reduction of TKI dose is a current practice to maintain efficacy while reducing the occurrence of side effects.